Local structure of semicrystalline P3HT films probed by nanofocused coherent X-rays. Issue 11 (20th February 2015) - Kurta, Ruslan P.; Grodd, Linda; Mikayelyan, Eduard; Gorobtsov, Oleg Y.; Zaluzhnyy, Ivan A.; Fratoddi, Ilaria; Venditti, Iole; Russo, Maria Vittoria; Sprung, Michael; Vartanyants, Ivan A.; Grigorian, Souren
Abstract : Spatially resolved x-ray study of semicrystalline P3HT films reveals nanoscale inhomogeneity of the conjugated network, as well as structural variations induced by Au nanoparticles. Abstract : The hidden structural properties of semicrystalline polymer films are revealed by nanofocused X-ray scattering studies. X-ray cross-correlation analysis (XCCA) is employed to diffraction patterns from blends of poly(3-hexylthiophene) (P3HT) with gold nanoparticles (AuNPs). Spatially resolved maps of orientational distribution of crystalline domains allow us to distinguish sample regions of predominant face-on morphology, with a continuous transition to edge-on morphology. The average size of crystalline domains was determined to be of the order of 10 nm. As compared to pristine P3HT film, the P3HT/AuNPs blend is characterized by substantial ordering of crystalline domains, which can be induced by Au nanoparticles. The inhomogeneous structure of the polymer film is clearly visualized on the spatially resolved nanoscale 2D maps obtained using XCCA. Our results suggest that the observed changes of the polymer matrix within crystalline regions can be attributed to nanoconfinement in the presence of gold nanoparticles.